Relationship ushul Fiqh, Qowa’id Fiqih dan Maqashid Al- Syariah With Islamic Economy - Nst, Venny Fraya Hartin; Nasution, M. Yasir; Sugianto, Sugianto (ITB AAS INDONESIA Surakarta, 2024)
Current Islamic Economy One of the main challenges is the low level of sharia financial literacy among the public. This causes the public to still have low interest in using sharia financial products and services. Another challenge is the lack of research and development in the field of Islamic economics and the lack of application of Islamic economics in business practices in Muslim countries. Therefore, efforts are needed to increase sharia financial literacy among the public, increase research and development in the field of Islamic economics, and apply Islamic economics in business practices in Muslim countries. Researchers decided to use qualitative research methods. Researchers use qualitative research methods because the opinions of each expert and practitioner are definitely different, a science can be very solution and relevant if applied at one time, but it could be useless if applied at a different time. Ushul fiqh in Islamic economics can be applied not to economics but to an economic system. Because the system is a regulation that requires a basic set of foundations that are qath'i based on revelation. The role of Ushul Fiqh as a methodology for developing economic systems in order to answer all contemporary economic problems. Meanwhile, in its application, Jazuli classifies qawa'id into six different areas, namely mahdhah (special) worship, ahwal as-Syahshiyyah (personal and family matters), mu'amalah maaliyah (economic transactions), jinayah (criminality), siyasah ( politics), and fiqh qadhaya (procedural and judicial law). Among the most basic qawa'id in this matter is